Translation and validation of NIOSH worker’s well-being questionnaire among healthcare workers (Wellbq) - Sampil, Nionella Stephen (2023)
Introduction: The measurement of a worker’s well-being is multidimensional that includes the work life of a worker, mental and physical condition, positive feelings, negative feelings, workplace environment, and workplace safety outside of work life. As we progress toward developing nations and countries, the measurement of workers’ well-being is increasingly being prioritized. NIOSH Worker’s Well-being Questionnaire is developed to measure workers’ well-being holistically. This study aims to establish the validity and reliability of this instrument before it can be used due to the cultural, language, and environmental differences between the Western and Eastern populations. Objectives: To translate to Malay language and to determine the validity and reliability of the Malay version NIOSH Worker’s Well-Being Questionnaire among healthcare workers in Hospital Universiti Sains Malaysia. Methods: A cross-sectional study involving a web-based survey was employed among healthcare workers at Hospital Universiti Sains Malaysia, Kubang Kerian. The study involved Forward and Backward Translation of the NIOSH Worker Well-being Questionnaire (WellBQ) to Malay version with Content Validation and Face Validation, and Confirmatory Factor Analysis (CFA) to determine the construct validity. Participants were recruited using a random sampling method through a selection of emails to healthcare workers. Descriptive, confirmatory factor analysis was applied in the statistical analysis. Results: Four expert panels were involved in content validation for the translation phase, and 30 medical officers were to rate the Face validation process. The CVI was calculated to be 0.92 for both S-CVI/Ave, and the FVI score was calculated to be 0.98, indicating that all items in the questionnaire are relevant to the domain, clear, and comprehensible. For the Confirmatory Factor Analysis phase, a total of 366 respondents participated in this study, the majority of the respondents being female (76%), Malay ethnicity (97.5%), between 30 to 44 years old (71%), works as nurses (52.7%) and holding education level of Diploma (63.9%) with permanent post (91.3%). The final measurement model of CFA had fit indices: CFI = 0.841, TLI = 0.834, RMSEA = 0.053, χ2 / df = 2.008. The fit indices were within the acceptable range. The composite reliability ranged from 0.603 to 0.963. Conclusion: The final model for Confirmatory Factor Analysis showed a reasonably acceptable model fit, valid and reliable after model revision of higher-order factors and after removing nine items. The translated Malay version of the NIOSH Worker’s Well-being Questionnaire comprised 117 items across five domains/factors. The questionnaire is valid and reliable for healthcare workers in local settings.